EDUCATIONAL SERVICES FOR TRAINING OF UNDERGRADUATE STUDENTS OF ACCOUNTING (2014) - Chumpitaz Ramos, Domingo Guzmán (2015)
This research aims to document and provide information to our authorities, teachers, administration staff and students about the quality of educational services for the professional training of undergraduate students of the final year of the School of Accounting Sciences of San Marcos (2014). This study was accomplished by doing fieldwork, the instrument applied was a questionnaire for students of Accounting School. Out of all students, a sample of 153 students was taken. The information was collected, stratified sampling was done and within each stratum simple random sampling was performed again. The information was stored in the statistical software SPSS 22.The study consisted first, in a descriptive study of two-dimensional educational services: educational service (infrastructure, administrative services and academic teaching and learning) and professional training (cognitive competences and abilities and skills). A correlational study was then performed using a suitable correlation coefficient, the statistic test Tau-b of Kendall. With this ratio, we conducted an analysis and interpretation of the results and concluded that there is a strong correlation between the services provided by the faculty and the training students have received.